Perancangan Sistem Deteksi Kebocoran Pipa Berbasis Internet of Things - Azizah, Fadila Nur; G. Drantantiyas,, Nike Dwi; Gani, Ferizandi Qauzar (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2025)
This research discusses the implementation of a prototype system to detect leaks in water pipes using water flow and ultrasonic sensors, applied to a web-based Internet of Things (IoT) for real-time monitoring. The aim of this research is to identify pipe leaks analyzed against flow rate and pressure. The system is designed considering the system design analysis using hardware, software, and web interface design for data visualization and control. The results of this study show that the water flow and ultrasonic sensors have high accuracy and precision with low error rates. Functional testing of the system was carried out through several experiments, both with and without leaks, and showed that the system works well in monitoring flow rates and water levels. However, some discrepancies were found in the readings during leak testing, indicating the need for further evaluation of the sensor code. Overall, this research was successful with real-time data accessible through the web interface.